Solitary juvenile polyp as a cause of elevated faecal calprotectin in an adult. (30th July 2018) - Hodgson-Parnell, Lara; Spence, Olivia; Chapple, Keith
Abstract : Faecal calprotectin (FCP) levels are commonly measured in both primary and secondary care as an adjunct to the diagnosis of inflammatory bowel disease (IBD). Juvenile polyps are a rare form of colonic polyp found in both adults and children. We present a case of an adult patient who presented with a very high FCP level, which subsequently normalised following removal of a solitary colonic juvenile polyp. There was no evidence of IBD. Elevation of FCP levels due to this type of colonic pathology have not previously been described in the literature.